Missing middle housing : thinking big and building small to respond to today's housing crisis - Parolek, Daniel G.; Nelson, Arthur C. (Island Press, 2020)
Daniel Parolek, an architect and urban designer, illustrates the power of Missing Middle housing types-such as duplexes, fourplexes, and bungalow courts- to meet today's diverse housing needs. With the benefit of beautiful full-color graphics, Parolek goes into depth about the benefits and qualities of Missing Middle Housing, explains why more developers should be building them, and defines the barriers cities need to remove to enable them to be built. Parolek proves that density is too blunt of an instrument to effectively regulate for twenty-first-century housing needs. Whether you are a planner, architect, builder, or city leader, Missing Middle Housing will help you think differently about how to address housing needs for today's communities.